Ridge splitting using autogenous bone wedge versus the conventional intercortical augmentation technique in horizontally deficient anterior maxilla: a randomized clinical trial - Mohammed Omara; Sameh Mekhemer; Sally Mansour; Yasmin Ahmed (BMC Oral Health)
Abstract Objectives This study aims to evaluate the quality and quantity of gained and maintained bone width after Ridge splitting utilizing autogenic bone wedge versus mixed bone particles for horizontal ridge augmentation in the anterior aesthetic zone. Materials and methods This randomized clinical trial included 20 patients with horizontally deficient anterior maxillary alveolar ridges. Patients were divided equally into two groups. Group I received an autogenous bone wedge harvested from the chin area to be placed intercotically after ridge splitting (intervention group). Group II received mixed bone particles of autogenic and xenogeneic bone placed intercortically after ridge splitting (control group). Radiographic assessment of gained and maintained alveolar bone width at three vertical levels was performed using CBCT at three-time intervals (preoperative, immediate postoperative, and 6 months postoperative). Histologic and histomorphometric analysis of core biopsy harvested immediately before implant placement was also performed to assess bone quality and % of newly formed bone area using H&E and Mansons trichrome stains. Collected data were conducted for statistical analysis. Results The outcome of the studied grafts showed a significant increase of the immediate postoperative bone width in the control group more than the intervention group, with a mean difference from the preoperative bone width (2.17 ± 1.10) mm for the control group and only (1.44 ± 0.66) for the intervention group. In contrast, the 6-month postoperative bone width was decreased in both groups with a mean difference from the immediate postoperative bone width (1.21 ± 0.54) in the control group (p-value < 0.001) compared to only (0.41 ± 0.50) in the intervention group (p value = 0.135); this statistical data revealed that the bone wedge technique of the intervention group helped to maintain the gained bone width more than the packed bone particles of the control group. Moreover, the intervention group showed higher value and quality of newly formed mature bone with well-formed havarsian canals than the control group, which showed lower bone quality of osteoid and fibrous tissue with remnants of xenogenic bone particles microscopically. Conclusions The two-stage ridge-splitting procedure using an interposition bone wedge is an effective method for horizontal ridge augmentation in the horizontally deficient anterior maxilla. Clinical relevance The two-stage Ridge splitting with an inter-positional bone wedge ensures better bone width maintenance and quality. Trial registration The study was registered on ClinicalTrials.gov on 24/07/2024 under the registry number “NCT06529653”. It adhered to the Declaration of Helsinki on medical research ethics and received approval from the Institutional Research Ethics Committee of the Faculty of Dentistry, Cairo University (IRB number: 161022).